2012
DOI: 10.1159/000345234
|View full text |Cite
|
Sign up to set email alerts
|

Structural Neuroimaging of Concomitant Depressive Symptoms in Amnestic Mild Cognitive Impairment: A Pilot Study

Abstract: Late-life depression (LLD) and amnestic mild cognitive impairment (aMCI) can both denote prodromal Alzheimer’s disease. While the two concepts share common clinical features, differential diagnosis between them is crucial. The objective of this pilot study was to explore differences in terms of the hippocampal (HC) and entorhinal cortex (EC) volume reduction between LLD and aMCI patients with (aMCI/D+ group) or without (aMCI group) depressive symptoms. Six LLD, 6 aMCI, and 6 aMCI/D+ participants were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 172 publications
1
7
0
Order By: Relevance
“…Indeed, although depressed and non-depressed aMCI participants in this study were comparable in terms of their memory performance on clinical tasks, and indeed recalled comparable quantities of items on the experimental task, the quality of the information remembered differed significantly. In addition, considering that behavior is an indicator of brain vulnerability, results from this study add to those of previous work (Brunet et al, 2011;Morin et al, 2012;Callahan et al, 2014Callahan et al, , 2016 to imply the likely existence of distinct neurobiological or neurofunctional manifestations in aMCI, aMCI/D+, and LLD. This necessitates further investigation using imaging measures, but we might speculate about plausible mechanisms by which depressive symptoms affect emotional memory.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Indeed, although depressed and non-depressed aMCI participants in this study were comparable in terms of their memory performance on clinical tasks, and indeed recalled comparable quantities of items on the experimental task, the quality of the information remembered differed significantly. In addition, considering that behavior is an indicator of brain vulnerability, results from this study add to those of previous work (Brunet et al, 2011;Morin et al, 2012;Callahan et al, 2014Callahan et al, , 2016 to imply the likely existence of distinct neurobiological or neurofunctional manifestations in aMCI, aMCI/D+, and LLD. This necessitates further investigation using imaging measures, but we might speculate about plausible mechanisms by which depressive symptoms affect emotional memory.…”
Section: Discussionsupporting
confidence: 69%
“…It is possible that performance in participants with aMCI/D+ is the result of neurobiological changes, potentially involving the hippocampus and/or the amygdala. Hippocampal atrophy has been associated with both aMCI and depression, independently (Morin et al, 2012) and correlates with recall of emotional pictures (Schultz et al, 2009). Similarly, amygdalar lesions are known to be present in early AD (Klein-Koerkamp et al, 2012) and in depressed seniors (Burke et al, 2011), and are thought to contribute to the disruption of emotional processes involved in emotional memory enhancement (Kensinger and Leclerc, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have explored brain structural changes in a depressed, cognitively impaired geriatric population; these studies reported that late-life depression was not significantly associated with lobar gray or white matter atrophy [43] but, it was significantly associated with hippocampus and left entorhinal cortex [44] . The mechanisms underlying depressive symptoms in cognitively impaired patients are unclear.…”
Section: Discussionmentioning
confidence: 99%